(untitled) (Quarterly Journal of Econometrics Research, 2015)
This study was conducted to determine the financial feasibility of African weaver ants (Oecophylla longinoda) as biological control agents in cashew and mango orchards. It was compared to chemical insecticides and control based on the experimental data in 2012/13 and 2013/14 cropping seasons. Three important discounted financial indicators were used in the study; they are the Net Present Value (NPV), Benefit-Cost Ratio (BCR) and Internal Rate of Return (IRR). Three scenarios concerning the increase of costs and benefits were used. The results of the study showed that all indicators for financial feasibility analysis were positive and accepted in each treatment. In cashew, African weaver ant without feeding indicated highest NPV (TZS 32 640), BCR (2.5:1) and IRR (57%). In mango, conflicting results were observed in feasibility ranking. But African weaver ants without feeding gave highest acceptable NPV of TZS 66 926. The three scenarios showed that setting much higher costs and benefits at five percent the NPV for African weaver ant was highest than other treatments. The findings of this study suggest that African weaver ant without feeding are financially feasible to be adopted and was recommended.